Effect of sensory integration ability on the academic achievement of elementary students in grades I to III - Harefa, Edward (Institute of Computer Science (IOCS), 2025)
To examine the effect of sensory integration on the academic achievement of elementary school students. This study was conducted on 151 elementary students in grades I to III in elementary schools in Gunungsitoli City, North Sumatra Province, using the sensory integration development rating scale. The development of students’ sensory integration ability was relatively stable in early elementary school and there were significant gender differences (F = 6.632, p = 0.01); sensory integration ability explained 16.9% of the variance in students’ academic achievement and 27.8% of the variance in girls' academic achievement; the learning ability dimension of sensory integration ability significantly affected students’ academic achievement (p = 0.005). The proprioceptive dimension (p = 0.012) had a significant effect on girls' academic achievement. There were gender differences in the performance of sensory integration skills between male and female elementary school students in grades I to III and the effect on academic achievement